Bowman-Birk inhibitors, proteasome peptidase activities and colorectal pre neoplasias induced by 1,2-dimethylhydrazine in Swiss mice. - Carli, Alessandra de Paula (2012)
Bowman-Birk inhibitors (BBIs) are protein molecules containing two inhibitory domains for enzymes similar to trypsin and chymotrypsin. Interest in these inhibitors arose from their properties against the cancer chemically induced by 1,2-dimethylhydrazine (DMH). In this study the effect of two BBI preparations (from Glycine max and Macrotyloma axillare) were evaluated for the prevention of colorectal neoplasia induced by intraperitoneal injections of DMH, given at a dose of 30 mg/kg, during 12 weeks. Mice treated with DMH presented histopathological alterations consistent with tumor development, augmented CD44 expression and increased proteasome peptidase activities. Lysosomal fractions, obtained from the intestines, were chromatographed in a Sepharose-BBI column and increased activity for trypsin and chymotrypsin-like proteases recovered from DMH-treated animals. In parallel, mice treated for eight weeks with BBIs showed a decrease in the chymotrypsin and trypsin-like proteasome activities compared to animals fed on normal diet. For the groups receiving simultaneous treatment with DMH and BBIs, dysplasic lesions were not observed and proteasome peptidase activities were similar to the control group after the 24th week. These results suggest that the mechanism by which BBIs could prevent the appearance of pre neoplastic lesions is associated with inhibition of both the lysosomal and proteasome- dependent proteolytic pathways.